2013
DOI: 10.1016/j.expneurol.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of retinal ganglion cell axon regeneration and pathfinding in whole mouse tissue after injury

Abstract: Injured retinal ganglion cell (RGCs) axons do not regenerate spontaneously, causing loss of vision in glaucoma and after trauma. Recent studies have identified several strategies that induce long distance regeneration in the optic nerve. Thus, a pressing question now is whether regenerating RGC axons can find their appropriate targets. Traditional methods of assessing RGC axon regeneration use histological sectioning. However, tissue sections provide fragmentary information about axonal trajectory and terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 47 publications
8
125
0
Order By: Relevance
“…In order to assess the pattern of growing axons, a three-dimensional analysis of the regenerating fibers was carried out in whole-mounted optic nerves after tissue clearing using a modified protocol previously described. 37,38 In the optic nerve segments situated between 100 and 300 mm past the lesion site, branched and unbranched axons could be distinguished, as well as axons that formed U-turns within this region (Figures 2e and f). We found that the proportion of branching axons did not significantly vary between Cnp-Cre þ / À xRtn4 flox/flox and Rtn4 flox/flox control mice (Figure 2g).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In order to assess the pattern of growing axons, a three-dimensional analysis of the regenerating fibers was carried out in whole-mounted optic nerves after tissue clearing using a modified protocol previously described. 37,38 In the optic nerve segments situated between 100 and 300 mm past the lesion site, branched and unbranched axons could be distinguished, as well as axons that formed U-turns within this region (Figures 2e and f). We found that the proportion of branching axons did not significantly vary between Cnp-Cre þ / À xRtn4 flox/flox and Rtn4 flox/flox control mice (Figure 2g).…”
Section: Resultsmentioning
confidence: 98%
“…47,48 Acting at two levels, the neuronal growth program activation with Zymosan and the blockade of Nogo-A signaling potentiated Our previous three-dimensional analyses revealed axonal guidance and patterning defects reflected by increased axonal U-turns and branching after growth induction in the injured optic nerve. 34,37 In the present study, we hypothesized that the myelin Nogo-A could have a role in axon guidance after optic nerve lesion. However, by examining individual growing axons in 3D, we found no significant difference in the proportion of branching or U-turn-forming axons between mouse genotypes.…”
Section: Moreover Inflammation-inducing Agents Such As Zymosan or Pamentioning
confidence: 90%
See 1 more Smart Citation
“…42 Therefore, sustained mTOR activity upon cytokine treatment is seemingly not necessarily required for switching RGCs into, but rather for maintaining the regenerative state. 17,42 Overall, the effects of PTEN knockout on PI3K/AKT activation, neuroprotection and optic nerve regeneration are much stronger compared with IS or direct cytokine application, 36,43,44 indicating a contribution of further targets beyond mTOR in these processes. Despite the remarkable effects of intrinsic PTEN or SOCS3 depletion on RGCs survival and regeneration, such approaches are, however, unfavorable from a clinical point of view due to their high cancerogenic potential and the requirement for pre-injury neuronal transduction to achieve optimal results.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ancillary activation of gp130 signaling upstream of PTEN with either CNTF bolus injections or IS further increases the number and length of regenerating axons of PTEN-depleted RGCs. [23][24][25] However, this approach is unfavorable as therapeutic treatment, since it requires neuronal transduction weeks prior to CNS injury and might increase the risk of cancer development post-treatment. [17][18][19] Instead of genetically deleting intracellular inhibitors, we hypothesized that it might be possible to boost axon regeneration by directly enhancing the cytokine-induced stimulus.…”
Section: Introductionmentioning
confidence: 99%